ENVIRONMENTAL-INDUCED DISPLACEMENT: POTENTIAL PROTECTION UNDER INTERNATIONAL LAW? - Irawati Handayani; Anisa Fauziah (Faculty of Law, Universitas Sebelas Maret, 2020)
Climate change, environmental degradation, and natural disasters are some of the push factors of cross-border displacement. The consequence of this movement is the loss of legal protection from the country of origin of the displaced persons. They are not categorized as refugees as such and no international law specifically regulates the protection of climate displaced persons. This paper will try to analyze the legal protection of climate refugees based on international law. The paper elaborates the context of migration caused by climate change and its relevance with the 1951 Convention on the Status of Refugee, possibility of interpretation of the convention to cover environmental induced displacement and protection under international human rights instruments. The research concludes that it is quite difficult to include climate change-induced displacement under the 1951 Convention on the Status of Refugee even through interpretation. However, it does not mean that the people cannot be protected. International law, especially International Human Rights Law extends protection to peoples belongs to that group.